Imbalance in redox system of rat liver following permethrin treatment in adolescence and neonatal age. (22nd May 2013) - Gabbianelli, Rosita; Palan, Matyas; Flis, Damian Jozef; Fedeli, Donatella; Nasuti, Cinzia; Skarydova, Lucie; Ziolkowski, Wieslaw
Abstract: 1.  The effect of different permethrin treatments on the redox system of rat liver, is presented. Two types of oral administration were chosen: (i) sub-chronic treatment (1/10 of LD50 for 60 days) during adolescence (5 weeks old) and (ii) sub-acute treatment (1/44 of LD50 for 15 days) during early life (from postnatal days 6–21). 2.  The results show that adolescent permethrin treatment induces damage to the liver redox system, increasing lipid and protein peroxidation and reducing membrane fluidity in the hydrophilic--hydrophobic region of the bilayer. In addition, glutathione peroxidase (GPx) and GSH levels resulted decreased, while glutathione transferase (GST) and catalase (CAT) levels increased. 3.  The rats treated in early life with permethrin and sacrificed in adult age, showed less signs of damage compared to those exposed during adolescence in which lipid peroxidation was increased by 32%, whereas for the first group the raise was only 11%. Moreover, fluidity improved in the deeper hydrophobic membrane region of the treated group, while the level of CAT was significantly lower compared to the control one. 4.  Although sub-chronic treatment increased CAT and GST and decreased GPx and GSH levels, the present data suggest that a shorter exposure to permethrin during neonatal age decreased CAT level and it could represent an important risk factor for the onset of long-term liver damage.